Mechanism of Action of Exercise in Regulating Spontaneous Hypertension through the Janus Kinase 2/Signal Transducer and Activator of Transcription 3 Signaling Pathway - Yu Li; Xiaoju Song; Lianjing Dai; Yangyi Wang; Qiong Luo; Lei Lei; Yunfei Pu (Journal of Physiological Investigation)
Although blood pressure can be regulated to normal levels through drug intervention, the prognosis for patients remains bleak, and there is an urgent need to find a new way to prevent or reverse hypertension and its adverse consequences. Some studies have shown that hypertension can be effectively improved by exercise training, but the exact manner in which it works is not completely comprehended. Using spontaneously hypertensive rats (SHR) and Wistar-Kyoto rats as models, an 8-week exercise intervention was adopted to detect the blood pressure, heart rate (HR), glucose tolerance, and insulin sensitivity. Histopathological changes in rat myocardium were observed using H and E staining and Masson staining. Different kits were used to detect the inflammation and oxidative stress in rats. Finally, the Janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) pathway-related proteins were examined by Western blot. After exercise, SHR rats showed a decrease in blood pressure and HR level, and an increase in glucose tolerance and myocardial insulin sensitivity. Exercise reduced SHR cardiomyocyte cross-sectional area and collagen deposition index, improved cardiac function, and decreased inflammation and oxidative stress. In addition, exercise can modulate the JAK2/STAT3 pathway, and when combined with JAK2 kinase inhibitor, it has an even greater effect on SHR. In conclusion, exercise could reduce blood pressure, inflammation, and oxidative stress, improve glucose tolerance and insulin sensitivity in SHR rats through modulating the JAK2/STAT3 pathway.